Daya Hidup Spermatozoa Babi Landrace Pada Pengencer Alami Air Kelapa Yang Di Suplementasi Berbagai Level Konsentrasi Sari Buah Pisang Kepok (Musa paradisiaca L.) - Alexandra Pallo Sungga; Nancy D.F.K Foeh; Cynthia D Gaina (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
The aim of this research is to study the survival of Landrace pig spermatozoa on natural diluents of coconut water supplemented with kepok banana juice (Musa paradisiaca L.). This research was conducted in February 2020-March 2020. Fresh cement collected from male Landrace pigs with ± 2 years of age was approved by an adult and in a healthy condition, then macroscopic, microscopic examination and cement dilution were conducted at the Veterinary Reproduction Laboratory of FKH Undana. This study uses 2 control groups (K0, K1) and 5 training groups (P1, P2, P3, P4, P5). The results of this study indicate that the first study using a low dose of 100 µL kepok banana juice (Musa paradisiaca L.) into cement dilution gave the best results in maintaining the viability of spermatozoa, seen from the high motility and viability values (65.00±3,54;71.50±2.26) with a shelf life of up to 28 hours.